Establishment of a new genus for Abraximorpha heringi and A. pieridoides (Lepidoptera: Hesperiidae: Pyrginae: Tagiadini) - Huang, Zhen-Fu; Chiba, Hideyuki; Wang, Min; Fan, Xiao-Ling (Zootaxa, 2016)
A new hesperiid genus, Albiphasma gen. nov., is described with Abraximorpha heringi as the type species. The new genus consists of two species: Al. heringi comb. nov. and Al. pieridoides comb. nov. The genitalia and hair tuft on the hind tibiae suggest that the new genus is related to the genus Pintara rather than the genus Abraximorpha to which the two species have been assigned. The geographic distribution is currently restricted to southern China and Vietnam. The adult, hind leg, wing venation and male genitalia of Al. heringi as well as relevant species are illustrated.